Influence of Promotional Strategies Through Social Media on The Purchase Decision of The Garskin Dimediate Word of Marketing - Karnawi Kamar; Eka Hendrayani; Sulistyo Budi Utomo; Widiastuti Furbani; Ratnawati Ratnawati (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
This study aims to determine: (1) The effect of promotional strategies through social media on purchasing decisions for Garskin products, (2) The effects of promotion strategies through social media on word of mouth marketing for Garskin products, (3) The influence of word of mouth marketing on product purchasing decisions for garskin, and (4) the effect of promotional strategies through social media mediated by word of mouth marketing on purchasing decisions for garskin products. The research design is a survey research. The sampling technique in this study used purposive sampling with a total sample of 145. Data analysis techniques were used to answer the research hypothesis were regression tests, path analysis (path analysis), and sobel tests. The results of this study indicate that: (1) There is a positive influence of promotional strategies through social media on purchasing decisions for Garskin products. This is evidenced by the t count of 8.664 with a significant value of 0.000 which is less than 0.05, and the regression coefficient has a positive value of 0.792, (2) There is a positive influence of promotional strategies through social media on word of mouth marketing for Garskin products. This is evidenced by the t count of 4.395 with a significant value of 0.000 which is less than 0.05, and the regression coefficient has a positive value of 0.395, (3) There is a positive influence of word of mouth marketing on purchasing decisions for Garskin products. This is evidenced by the t count of 4.821 with a significance value of 0.000 less than 0.05, and the regression coefficient has a positive value of 0.440 (4) There is an influence of promotion strategies through social media on purchasing decisions mediated by word of mouth marketing on Garskin products. This is evidenced by the mediation coefficient of 0.0906 which is positive and has a significance of 0.0217, less than 0.05.